Holding out for Christmas - Dailey, Janet (New York, NY : Kensington Publishing Corp., 2020)
"Conner Branch still hasn't stopped thinking about the sultry singer he spotted on stage during last year's Cowboy Christmas Ball. So imagine his surprise when he discovers the demure kindergarten teacher who comes home for the holidays to Branding Iron, Texas, is the very same woman. And once he's up close and personal with the mesmerizing Megan, he's downright determined to keep her by his side for good . . .If only Conner Branch were simply the star struck cowboy she once believed him to be, Megan wouldn't have to worry about losing everything to the rugged - and wildly romantic - rancher. With Christmas in the air, it's a little too easy to imagine spending the holidays, not to mention her whole life, wrapped in Conner's loving arms. But this songstress has hopes for a big career back in Nashville. And no little holiday romance will ever get in the way of that. So what's a woman to do when she finds herself facing down a love as bold and exciting as Texas itself?"--Publisher
Includes an excerpt of the book "Whirlwind" written by the author.
Keywords: Kindergarten teachers -- Fiction; Ranchers -- Fiction; Man-woman relationships -- Fiction; Christmas stories; Texas -- Fiction; Romance fiction